2023
DOI: 10.31004/obsesi.v7i5.5324
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Bahasa Inggris Awal pada Periode Linguistik Anak Usia Dini

Yesi Novitasari,
Danang Prastyo,
Ardhana Reswari
et al.

Abstract: Belakangan ini Lembaga PAUD berbondong-bondong memberikan pembelajaran bahasa inggris bagi anak diperiode linguistik. Penelitian ini bertujuan untuk mengetahui kemampuan awal anak dalam mendengarkan dan mengucapkan kosakata bahasa inggris pada periode linguistic. Penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan kuantitatif. Populasi penelitian ini mencakup anak pada Taman Kanak-Kanak. Selanjutnya peneliti melakukan penarikan sampling dengan teknik sampling jenuh dengan jumlah 28 Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…When this finding is compared with the elements of Jean Piaget's Learning Theory, it can be concluded that the finding possibly arose from the lack of material and activity readiness from the students, mainly because the material did not meet the students' interest (2) Rezeki (2021), in the research, entitled Children's Language Acquisition due to the Influence of Animation Film had finding that showed the words that Omar Hana used in the film influenced the children's language acquisition aged three years old and five years old. When this finding is compared with the elements of Jean Piaget's Learning Theory, it can be concluded that the finding possibly arose from the activities readiness of the children; and (3) Novitasari et al, (2023) in their research, entitled Kemampuan Bahasa Inggris Awal pada Periode Linguistik Anak Usia Dini find that children able to listen to related songs to the vocabulary that they learn, lower than the first one was able to listen to random vocabulary, lower than the second one was able to listen to short stories, lower than the third one was able to listen to vocabulary in sequence, and lower than the fourth one was able to listen to the pictures pointing instructions according to the vocabulary they hear. When this finding is compared with the elements of Jean Piaget's Learning Theory, it can be concluded that the finding possibly arose from the fulfillment of the element of characteristics, cognitive development, material readiness, and, most importantly, the role of the teacher because the stage of students in their research is under elementary school students.…”
Section: Resultsmentioning
confidence: 96%
“…When this finding is compared with the elements of Jean Piaget's Learning Theory, it can be concluded that the finding possibly arose from the lack of material and activity readiness from the students, mainly because the material did not meet the students' interest (2) Rezeki (2021), in the research, entitled Children's Language Acquisition due to the Influence of Animation Film had finding that showed the words that Omar Hana used in the film influenced the children's language acquisition aged three years old and five years old. When this finding is compared with the elements of Jean Piaget's Learning Theory, it can be concluded that the finding possibly arose from the activities readiness of the children; and (3) Novitasari et al, (2023) in their research, entitled Kemampuan Bahasa Inggris Awal pada Periode Linguistik Anak Usia Dini find that children able to listen to related songs to the vocabulary that they learn, lower than the first one was able to listen to random vocabulary, lower than the second one was able to listen to short stories, lower than the third one was able to listen to vocabulary in sequence, and lower than the fourth one was able to listen to the pictures pointing instructions according to the vocabulary they hear. When this finding is compared with the elements of Jean Piaget's Learning Theory, it can be concluded that the finding possibly arose from the fulfillment of the element of characteristics, cognitive development, material readiness, and, most importantly, the role of the teacher because the stage of students in their research is under elementary school students.…”
Section: Resultsmentioning
confidence: 96%
“…Language development is one of the developments that children must achieve and should not escape the attention of educators and parents. According to Novitasari et al (2023), children's language development is divided into several periods, pre-linguistic period (0-1 years) and linguistic period (1-5 years). Training activities in the framework of community service to pre-school teachers are quite important and appropriate activities to prepare teachers to equip students who are already | 535 | English teaching method training to improve the competency of kindergarten teachers Rizkiana Maharddhika, Mushoffan Prasetianto, Hafida Ruminar, Dian Islami Prasetyaningrum in the linguistic period.…”
Section: Discussionmentioning
confidence: 99%